Kejhung's Oral Tradition As An Educational Media In Strengthening The Profile Of Pancasila Students Based On Madura's Local Wisdom - Sri Utami; Victor Marolitua L Tobing; Wahyu Widayati (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2022)
The purpose of this research isdescribes kèjhung as an educational medium in strengthening the profile of Pancasila students based on Madurese local wisdom. This study used a qualitative descriptive approach and the ethnopedagogic method of the researcher as a human instrument. This research involves hermeneutic and ethnopedagogical analysis methods. Hermeneutics is used to reveal contextual conditions. This research uses data in the form of kejhung text which contains values of character education andin the form of rhymes and performed in Proppo District, Pamekasan Regency.The result of the research is that kejhung contains many religious values, politeness values, social values, and mutual cooperation values so that Madura kejhung can be utilized.aseducational mediain strengthening the profile of Pancasila students